Do teachers misbehave? Aggression in school teams. Issue 6 (7th September 2015) - Ben Sasson, Dvora; Somech, Anit
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Despite growing research on school aggression, significant gaps remain in the authors' knowledge of team aggression, since most studies have mainly explored aggression on the part of students. The purpose of this paper is to focus on understanding the phenomenon of workplace aggression in school teams. Specifically, the purpose of the study was to examine whether team affective conflict in school teams mediates the relationship between team injustice climate (distributive, procedural, and interpersonal injustice climate) and team aggression. Design/methodology/approach – Data were collected from a survey of 43 school teams at different schools using questionnaires. Findings – Results showed that team affective conflict played a role in fully mediating the relationship of team procedural and interpersonal injustice climate to team aggression. Research limitations/implications – The present results empirically support the notion that workplace aggression can be considered not only an individual phenomenon but also a team phenomenon. Furthermore, it highlights the significance of organizational factors in predicting this phenomenon. The study should serve to encourage principals to reduce the level of team aggression and develop a supportive climate characterized by fair procedures and respect. Originality/value – A review of the literature also reveals that little investigative effort has been made by scholars to examine aggression on the part of teachers. Evidence for this can be seen in the scarcity of publications on this topic. The current literature's call to address this issue in schools and at the team level (Fox and Stallworth, 2010) stimulated the present study by highlighting the importance of exploring the contextual factors, rather than the individual ones, responsible for school team aggression.